Developing a Decision Support Application for Selecting New Scholars - Te, Jonathan Mark N.; Rivera, Albert Geroncio Y. (Silliman Journal, 2022)
The Scholarship Decision Support System was developed to allow the Scholarship and Student Aid Division (SSAD) of Silliman University to generate the general ranking list and valedictorian list that would provide support to the Scholarship and Aid Committee (SAC) in their deliberation for awarding scholarships to applicants. The decision support system provides a list that also matches an applicant to a scholarship based on the scholarship’s requirements in terms of the course, gender, graduation honor, and province or region of origin. In generating the ranking lists, the SSAD follows a rating system to determine the rank of each applicant. The applicant’s high school general average, number of siblings, and parents’ annual family income are taken into consideration and are given corresponding ratings based on the SSAD’s criteria. Microsoft Visual C# 2010 and MySQL Server 5.6 were used in developing the decision support system. After initial completion of system, refinement was done through prototype reviews. The prototype reviews provided several improvements for the system that were not initially seen. The refinements were immediately taken into consideration and applied to the system. Test cases were used to fully test if the features of the system work as originally intended. The test case results showed that all of the features worked and that the system had passed the test.